(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Currently, one of the important factors is the development of the hotel industry, which is one of the main tourism industries in the country. But most of them are poorly organized. Their level of service does not meet international standards. Currently, there are a number of world class hotels in Uzbekistan. Examples include Inter Continental, Central, Shodlik Palace, Afrosiyob and other hotels. These hotels are currently hosting various meetings, conferences and seminars. There are enough conditions and services to receive foreign tourists.